The LAPEF: An Interdisciplinary Laboratory of Research - Busacchi, Vinicio (Natureza Humana - Revista Internacional de Filosofia e Psicanálise, 2023)
This paper introduces the LAPEF, or Laboratory of Psychoanalysis, Hermeneutics and Phenomenology, an interdisciplinary Italian laboratory that gathers philosophers, psychoanalysts and psychiatrists from various schools who share a common scientific and humanistic interest for a holistic approach on the human being and its condition. The text outlines LAPEF’s major theoretical-philosophical and procedural-scientific characters, along with its significant commitments and achievements to fostering both an interdisciplinary and inter-institutional collaboration. Furthermore, it highlights LAPEF's endeavors in research, education and cultural engagement.